Cognitive, Behavioural and Psychiatric Phenotype in 22q11.2 Deletion Syndrome - Philip, Nicole (2011)
22q11.2 Deletion syndrome has become an important model for understanding the pathophysiology of neurodevelopmental conditions, particularly schizophrenia which develops in about 20–25% of individuals with a chromosome 22q11.2 microdeletion. From the initial discovery of the syndrome, associated developmental delays made it clear that changes in brain development were a key part of the expression. Once patients were followed through childhood into adult years, further neurobehavioural phenotypes became apparent, including a changing cognitive profile, anxiety disorders and seizure diathesis. The variability of expression is as wide as for the myriad physical features associated with the syndrome, with the addition of evolving phenotype over the developmental trajectory. Notably, variability appears unrelated to length of the associated deletion. Several mouse models of the deletion have been engineered and are beginning to reveal potential molecular mechanisms for the cognitive and behavioural phenotypes observable in animals. Both animal and human studies hold great promise for further discoveries relevant to neurodevelopment and associated cognitive, behavioural and psychiatric disorders.